Activation of ventral tegmental area vesicular GABA transporter (Vgat) neurons alleviates social defeat stress-induced anxiety in APP/PS1 mice - Yao, Di; Li, Rong; Kora, Musa; Huang, Hongqing; Liu, Xinghua; Gong, Song (Frontiers in Aging Neuroscience, 2023)
Introduction Alzheimer’s disease (AD) is a progressive neurodegenerative disease that results in cognitive impairment and is often accompanied by anxiety. In this study, we investigated whether the activation of VTAVgat neurons could reduce anxiety in APP/PS1 mice. We hypothesized that acute social defeat stress (SDS) would lead to anxiety in APP/PS1 mice, and that the activation of VTAVgat neurons would alleviate this anxiety. Methods We exposed APP/PS1 mice to acute SDS and assessed anxiety using the open field test and elevated plus-arm test. Activated VTAVgat neurons was tested by cfos staining. Sleep quality was detected using electroencephalogram after SDS or non-SDS procedure. Sleep duration, sleep latency, and non-rapid eye movement (NREM) percentage were analyzed. VTAVgat neurons were chemogenetically activated by deschloroclozapine. Results Our results showed that acute SDS led to anxiety in APP/PS1 mice, as evidenced by increased anxiety-related behaviors in the open field and elevated plus-arm tests. Activation of VTAVgat neurons by SDS led to an increase in sleep duration, primarily due to a decrease in sleep latency and an increase in NREMs. However, the quality of sleep was poor. Chemogenetical activation of VTAVgat neurons improved sleep quality and relieved SDS-induced anxiety. Furthermore, the anxiety state correlated negatively with sleep duration and NREM percentage and correlated positively with theta power density in APP/PS1 mice. Discussion Our study provides evidence that the activation of VTAVgat neurons alleviates SDS-induced anxiety in APP/PS1 mice, suggesting that poor sleep quality may exacerbate anxiety in AD. These findings may have important implications for the treatment of anxiety in AD, as targeting VTAVgat neurons could be a potential therapeutic approach.